Adult plant leaf rust resistance QTL derived from wheat line CI13227 maps to chromosomes 2AL, 4BS, and 7AL. Issue 3 (11th May 2022) - Kolmer, James A.; Rouse, Matthew N.
Abstract: The winter wheat ( Triticum aestivum L.) line CI13227 has been characterized as having adult plant resistance to leaf rust caused by Puccinia triticina Eriks ( Pt ). Line CI13227 was crossed with the susceptible spring wheat 'Thatcher' (Tc) and a Tc*2/CI13227 F6 line with adult plant leaf rust resistance designated as 411A was derived. Line 411A was crossed with Tc to develop an F6 recombinant inbred line (RIL) population. The parents and 120 F6 lines were assessed for leaf rust severity at the flag leaf stage in five field plot tests from 2011 through 2015 and were genotyped for single‐nucleotide polymorphism (SNP) markers with the Illumina iSelect 90K wheat bead array. A total of 2, 384 SNP markers segregated among the RILs. Completely linked SNPs were removed, and 474 markers that covered 2, 605 centimorgans (cM) were used for linkage map construction. Quantitative trait loci (QTL) on chromosome 2AL with logarithm of odds (LOD) values 2.34–7.88, on chromosome 4BS with LOD values 1.35– 4.66, and on chromosome 7AL with LOD values 2.92–7.81 were associated with significant reduction in leaf rust severity in the field plot tests. Recombinant inbred lines that had combinations of two or three of the QTL had significantly lower leaf rust severity than RILs that lacked any resistance QTL. Kompetitive allele specific polymerase chain reaction (KASP) markers were developed for the SNPs that were closely linked with the three QTL to facilitate marker‐based selection of the leaf rust resistance in breeding programs. Core Ideas: Winter wheat line CI13227 has adult plant leaf rust resistance. QTL for adult plant leaf rust resistance from CI13227 were mapped to chromosomes 2AL, 4BS, and 7AL. KASP markers linked to the QTL regions were developed.